Scenario planning: a collage construction approach - Graham Saunders, Stephen (Foresight (Cambridge), 2009)
Purpose - The purpose of this paper is to suggest and recommend an alternative visual technique to collect scenario planning information. This visual technique is known as collage or papier collé.Design methodology approach - A case study example of using collage construction to collect scenario planning information is presented.Findings - Collage construction was deemed well suited to scenario planning as it overcome some of the problems of verbal communication techniques, providing an additional technique that allows the scenario planner to analyse information from multiple angles and sources. Through using multiple techniques, the scenario planner is able to increase "trustworthiness" of the data and analysis and build confidence that the future scenarios are "authentic", "believable" and "applicable".Research limitations implications - A major limitation of this study is that only one case study is presented. To ensure "trustworthiness" across a variety of industries and cultural contexts, further replication would be needed.Practical implications - Collage construction can prove to be a valuable additional tool for the scenario planner when verbal communication is limited or problematic.Originality value - This research recommends a scenario planning technique that does not necessarily rely on verbal communication skills.